Absent Right Side Iliac Arterial System, an Intraoperative Surprise during Live Related Recipient Renal Transplantation - Vijay Radhakrishnan; Rana Kumar; Datson George; G. P. Abraham (Case Reports in Transplantation)
Introduction. Renal transplantation has become the standard of care for patients with end stage renal disease. We present a rare case of an absent right sided iliac arterial system encountered during recipient renal transplantation. The presence of such vascular anomaly intraoperatively can present a technically challenging situation to the surgeon. Case Presentation. During a routine renal transplantation of a 34-year-old man, we encountered a complete absence of right side iliac arterial system and a prominent branch arising from left hemipelvis and coursing to the right lower limb and the urinary bladder. The artery to the bladder was divided and anastomosed end to end to the donor renal artery. Intraoperatively the renal perfusion and the urine output were good. A posttransplant magnetic resonance angiogram done six weeks later revealed good vascular supply to the kidney and the lower limb. Conclusion. Absent iliac artery on one or both sides is a rare phenomenon. The presence of it during an unanticipated renal transplant surgery can pose a significant technical challenge to the surgeons. We advocate routine assessment of pelvic vasculature before recipient renal transplant surgery so as to avoid a difficult situation like this.